Capitalism: what has gone wrong, what needs to change, and how it can be fixed. (8th November 2021) - Collier, Paul; Coyle, Diane; Mayer, Colin; Wolf, Martin
Abstract: The distinguished contributors to this issue of the Oxford Review of Economic Policy were asked to address the question of what has gone wrong with capitalism, what needs to change, and how can it be fixed. The objective behind the solutions discussed in these articles is to retain as far as possible the benefits of globalization, technology, and market processes, while addressing sources of disaffection and discontent by prioritizing convergence in attainable levels of earned incomes and wellbeing within and across countries. Three key ideas run through the articles. The first is the inadequate depiction of the individual in conventional economics as a person preoccupied with consumption and leisure. The second is widespread support for greater devolution to local decision-taking, and an emphasis on the importance of cooperation in communities. The third is the critique of economic orthodoxy implied by the concept of radical uncertainty. Together, these articles provide an inspiring assessment and reconceptualization of capitalism, and offer practical ways of addressing its deficiencies while preserving its merits.